Child-Drone Interaction in STEM education - Grahn, Lovisa; Großkopf, Birte (My University, 2022)
Drones are becoming more common in a variety of areas and more integrated in people’s everyday lives. One example of this is education, where drones have potential to spark children’s interest and help with teaching of STEM subjects like programming. By conducting an ethnographic study at a school in central Gothenburg, this thesis aims to explore the possibilities of using drones in education and what needs to be considered when doing so. The conclusions led to a set of design considerations within the themes of safety, battery life, communication between user and drone, collaboration, touch interaction and gesture. In addition to these, a support material was created based on the instruction manual for the Tello EDU drone and the most commonly asked questions from the children during the workshop. The intention is that teachers could use this material, or something similar, during lessons where the children work with drones.
Keywords: Child-robot interaction; social robots; child-drone interaction; drones; ethnography; education; workshop; STEM